In vitro selective inhibition of human UDP-glucuronosyltransferase (UGT) 1A4 by finasteride, and prediction of in vivo drug–drug interactions. Issue 2 (22nd January 2015) - Lee, Seung Jun; Park, Jung Bae; Kim, Doyun; Bae, Soo Hyeon; Chin, Young-Won; Oh, Euichaul; Bae, Soo Kyung
Highlights To our knowledge, inhibition of hepatic UGT isozymes by finasteride has not been explored. Of the seven hepatic UGTs, finasteride potently and selectively inhibited UGT1A4. Finasteride did not inhibit hepatic UGT1A1, 1A3, 1A6, 1A9, 2B7, and 2B15 activities. However, the Cmax of finasteride in patients is much lower than Ki of finasteride for UGT1A4. Finasteride is unlikely to cause clinically significant drug–drug interactions via UGTs inhibition.